Salinity and Alkalinity Problem and Fertility Status of some Soils of Chambal Commanded Area - Sharma, C. P.; Seth, S P. (Indian Forester, 1971)
A soil survey was undertaken to study the nature and extent of salinity problem and available nutrient status of the oils of Chambal Commanded Area. Possibility of reclaiming these soils and obtaining higher yields with fertilization has been indicated.